Multicenter, International Assessment of the Eighth Edition of the American Joint Committee on Cancer Cancer Staging Manual for Conjunctival Melanoma - Jain, Puneet; Finger, Paul T.; Damato, Bertil; Coupland, Sarah E.; Heimann, Heinrich; Kenawy, Nihal; Brouwer, Niels J.; Marinkovic, Marina; Van Duinen, Sjoerd G.; Caujolle, Jean Pierre; Maschi, Celia; Seregard, Stefan; et al. (JAMA Ophthalmology, 2019)
This case series assesses whether the eighth edition of the American Joint Committee on Cancer (AJCC) Cancer Staging Manual can be used to accurately estimate mortality rates of conjunctival melanoma.
CRIS-Team WoS Importer:2019-08-27